The Mediating Role of Turnover Intention on The Relationship Between Job Satisfaction and Employee Performance: Evidance From KSU Sinar Dana Mandiri Employees - Widyani, Anak Agung Dwi; Saraswati, Ni Putu Ayu Sintya; Wijaya, I Negah Basma (International Journal of Applied Business and International Management, 2019)
This study explores the links between job satisfaction, turnover intention, and employee performance. In particular, we investigate the mediating effect of turnover intention on the relationship between job satisfaction and employee performance in KSU Sinar Dana Mandiri. The research was based on primary data, and this research was conducted on the employee’s working in cooperative institution. The sample consisted employee of 32 respondents on KSU Sinar Dana Mandiri. Data were analyzed using Partial Least Square (PLS) analysis techniques to answer the problem formulation with the help of SmartPLS 3 program. Research finding are job satisfaction has a negative and significant effect on turnover intention, job satisfaction has a positive and significant effect on employee performance, turnover intention has a negative and significant effect on employee performance, and turnover intention variable is able to be a mediating variable between job satisfaction and employee performance.